2019
DOI: 10.7717/peerj.6817
|View full text |Cite
|
Sign up to set email alerts
|

Molecular serotyping of clinical strains ofHaemophilus (Glaesserella) parasuisbrings new insights regarding Glässer’s disease outbreaks in Brazil

Abstract: Glässer’s disease (GD) is an important infectious disease of swine caused by Haemophilus (Glaesserella) parasuis. Vaccination with inactivated whole cell vaccines is the major approach for prevention of H. parasuis infection worldwide, but the immunity induced is predominantly against the specific polysaccharide capsule. As a consequence, the available vaccines may not induce adequate protection against the field strains, when the capsules present in the vaccine strains are different from those in strains isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
1
15
0
4
Order By: Relevance
“…As in many other countries in Europe and all over the world [6,7,12,13,[23][24][25][26][27][28], serovar 4 is strongly represented in the present study with a portion of approximately 25% of our isolates belonging to this serovar. Similarly to recent studies from Northern Italy, the UK and Southern China [12,13,23], serovar 4 is the most important serovar in our collection, too, whereas in other countries serovar 5 (or serotype 5/12 respectively) appears to be more frequent [7,24,27,28].…”
Section: Serotypingsupporting
confidence: 72%
See 1 more Smart Citation
“…As in many other countries in Europe and all over the world [6,7,12,13,[23][24][25][26][27][28], serovar 4 is strongly represented in the present study with a portion of approximately 25% of our isolates belonging to this serovar. Similarly to recent studies from Northern Italy, the UK and Southern China [12,13,23], serovar 4 is the most important serovar in our collection, too, whereas in other countries serovar 5 (or serotype 5/12 respectively) appears to be more frequent [7,24,27,28].…”
Section: Serotypingsupporting
confidence: 72%
“…This is in contrast to older studies using gel immunodiffusion or indirect hemagglutination [5,7] and may well be attributed to the methodology as discussed for other pathogens [31]. However, there are also countries in Asia or South America where the proportion of non-typable isolates is large [26,27,32]. The studies from those countries were using the same molecular method which had initially been developed based on a collection of isolates mainly from the UK.…”
Section: Serotypingmentioning
confidence: 98%
“…The colonies from the brain tissue were pooled and used to inoculate supplemented PPLO broth and grown to an optical density of 0.7, and the cell density determined by flow cytometry and distributed in 1 mL aliquots of frozen medium [50 g/L of Skim Milk (Sigma-Aldrich, USA), 25 g/L of Tryptone (Sigma-Aldrich, USA) and 20% of glycerol (Sigma-Aldrich, USA)] and stored frozen at −80 • C. The purity of the pooled culture was confirmed by Gram staining and negative PCR analysis for A. pleuropneumoniae, P. multocida, B. bronchispetica, M. hyopneumoniae, M. hyorhinis, M. hyosynoviae but positive for G. parasuis. The capsular type of the pooled stock was determined by multiplex PCR using the strategy described by Espindola et al (11).…”
Section: Preparation Of a Standard Challenge Inoculummentioning
confidence: 99%
“…Recently, we have demonstrated that the commercially available vaccines in Brazil do not include the most prevalent SVs isolated from pigs suffering GD and that a substantial proportion of disease was caused by non-typeable (NT) strains that can likely represent at least nine new serovars ( Espíndola et al., 2019 ). This situation can easily explain why the veterinarians are still using massive amounts of antimicrobial molecules in animal feed to control the clinical presentation of GD during the nursery phase (Brazilian perspective, personal observation).…”
mentioning
confidence: 99%
“…Each of these isolates were from different farms and states with high pig production rates. In addition, after culture isolation, all samples were molecularly typified ( Espíndola et al., 2019 ). The susceptibility test was carried out by the microdilution assay (96 well plates, TPP, Swiss) according to the recommendations of the Clinical and Laboratory Standard Institute (2013) for A. pleuropneumoniae .…”
mentioning
confidence: 99%